Teaching Nature and Society – space for integration of concrete experiences of the child - Kisovar-Ivanda, Tamara (Rethinking childhood II: child and space, 2026)
In the pedagogical context, we sometimes encounter the attitude that, in the teaching of Nature and Society, there is a mechanical and successive merging of topics from the subject teaching, which we encounter in the upper grades of elementary school. For example, these include topics related to orientation in space, orientation in time, topics directed towards different life communities, etc. The subject Nature and Society promotes a multi-perspective and integrated networking of content from the child’s natural and social environment, in which the child should be provided with as many different concrete experiences as possible. Enabling the child to learn about the world in which they live in an integrated way—both through research and based on as many different multi-sensory experiences as possible—means creating a space in which they can develop freely. In the process of changing the status of the teaching subject Nature and Society and fragmentation of the subject areas, the principles of the primary level of elementary school education would be replaced by those of the subject classes in the upper grades of elementary school.